Leadership Discourse, Culture, and Corporate Ethics: CEO-speak at News Corporation - Amernic, Joel; Craig, Russell (2013)
We explore the language of leadership of global media mogul Rupert Murdoch in 2010, the year before the phone-hacking scandal in the UK came to public attention. Subsequent public enquiries in the UK exposed unethical conduct by staff of News Corporation, a global corporation whose Chairman and CEO was Rupert Murdoch. We focus on the ethical climate fashioned by ‘A Letter from Rupert Murdoch’ that appeared in the opening pages of the annual report of News Corporation for the year ended 30 June 2010. Plausibly, Murdoch’s discourse in that letter helped condition the inapt, unethical conduct of News Corporation staff. We highlight the cultural and ethical signs that were embedded in Murdoch’s letter and which reflected the company’s tone at the top and ethical values. We identify signs of a perverse leadership thinking that possibly help explain the inappropriate cultural values and ethical behaviours that were revealed subsequently in evidence presented to public inquiries.
Keywords: News Corporation; Rupert Murdoch; Leadership; Ethics; Discourse; Culture